Cronkhite-Canada Syndrome Mimicking COVID-19-related Symptoms - Kayo Miyawaki; Takaya Komori; Yoshihiro Ishida; Yuri Sakaguchi; Hajime Honjo; Masatoshi Kudo; Atsushi Otsuka (Medical Journals Sweden, 2022)
Abstract is missing (Short communication)